1998
DOI: 10.1055/s-2007-1001304
|View full text |Cite
|
Sign up to set email alerts
|

Flat Adenomas in the United Kingdom: Are Treatable Cancers Being Missed?

Abstract: The polyp-carcinoma hypothesis prompts colonoscopists to search only for polypoid lesions when screening for malignancy. A significant proportion of early colorectal neoplasms may therefore be missed. European colonoscopists require training in the recognition of flat elevated and depressed lesions in order to detect colorectal malignancies in their early stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
91
0
8

Year Published

2000
2000
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(102 citation statements)
references
References 0 publications
3
91
0
8
Order By: Relevance
“…It is likely that the biologic behaviour of NPG carcinomas is more aggressive than that of PG carcinomas. Many reports have analysed that flat and depressed lesions have a higher malignant potential than polypoid lesions, since flat and depressed lesions readily infiltrate deeper layers despite their small size (Crowford and Stromeyer, 1983;Wolber and Owen, 1991;Lanspa et al, 1992;Jaramillo et al, 1994;Rubio et al, 1994;Kudo et al, 1995a, b;Mitooka et al, 1995;Yokota et al, 1995;Fujii et al, 1998;Hart et al, 1998;Rembacken et al, 2000;Saito et al, 2001). A greater malignant potential in NPG carcinomas than in PG carcinomas is analogous to flat lesions containing depressed areas having greater malignant potential than polypoid adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that the biologic behaviour of NPG carcinomas is more aggressive than that of PG carcinomas. Many reports have analysed that flat and depressed lesions have a higher malignant potential than polypoid lesions, since flat and depressed lesions readily infiltrate deeper layers despite their small size (Crowford and Stromeyer, 1983;Wolber and Owen, 1991;Lanspa et al, 1992;Jaramillo et al, 1994;Rubio et al, 1994;Kudo et al, 1995a, b;Mitooka et al, 1995;Yokota et al, 1995;Fujii et al, 1998;Hart et al, 1998;Rembacken et al, 2000;Saito et al, 2001). A greater malignant potential in NPG carcinomas than in PG carcinomas is analogous to flat lesions containing depressed areas having greater malignant potential than polypoid adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…Estas inovações permitiram também o diagnóstico diferencial endoscópico entre lesões neoplásicas e não-neoplásicas (11,17,18,19,20,21,22) .…”
Section: Introductionunclassified
“…These lesions are thought to be de novo carcinomas because they have no adenomatous component. [4][5][6] The K-ras mutation has been detected much less often in flat or depressed colorectal tumours compared with exophytic tumours. 7,8 Recently, we reported that the RASSF1A gene, which regulates ras function, is frequently hypermethylated in flat or depressed tumours, 9 but this hypermethylation is only infrequently found in conventional colorectal cancers.…”
Section: Introductionmentioning
confidence: 99%